Have newer bearing surfaces changed expectations regarding the longevity of total hip arthroplasty?. (July 2020) - Engh, Jr., Charles A.; McAsey, Craig J.; Cororaton, Agnes D.; Ho, Henry; Hopper, Jr., Robert H.
Abstract : Aims: The purpose of this study is to examine six types of bearing surfaces implanted at a single institution over three decades to determine whether the reasons for revision vary among the groups and how long it takes to identify differences in survival. Methods: We considered six cohorts that included a total of 1, 707 primary hips done between 1982 and 2010. These included 223 conventional polyethylene sterilized with γ irradiation in air (CPE-GA), 114 conventional polyethylene sterilized with gas plasma (CPE-GP), 116 crosslinked polyethylene (XLPE), 1, 083 metal-on-metal (MOM), 90 ceramic-on-ceramic (COC), and 81 surface arthroplasties (SAs). With the exception of the COC, all other groups used cobalt-chromium (CoCr) femoral heads. The mean follow-up was 10 (0.008 to 35) years. Descriptive statistics with revisions per 100 component years (re/100 yr) and survival analysis with revision for any reason as the endpoint were used to compare bearing surfaces. Results: XLPE liners demonstrated a lower cumulative incidence of revision at 15 years compared to the CPE-GA and CPE-GP groups owing to the absence of wear-related revisions (4% for XLPE vs 18%, p = 0.02, and 15%, p = 0.003, respectively). Revisions for adverse local tissue reactions occurred exclusively among the MOM (0.8 re/100 year) and SA groups (0.1 re/100 year). The revision rate for instability was lower among hips with 36 mm and larger head sizes compared to smaller head sizes (0.2% vs 2%, p < 0.001). Conclusion: The introduction of XLPE has eliminated wear-related revisions through 15-year follow-up compared to CPE-GP and CPE-GA. Dislocation incidence has been reduced with the introduction of larger diameter heads but remains a persistent concern. The potential for adverse local tissue reactions with MOM requires continued follow-up. Cite this article: Bone Joint J 2020;102-B(7 Supple B):105–111.